Penerapan Teknik Camera Angle pada Film Kang Mak Indonesia Karya Herwin Novianto - Fabio Fahrezi Canavaro; Dani Manesah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The Indonesian film Kang Mak, directed by Herwin Novianto, effectively utilizes camera angle techniques to support the narrative and depict emotional dynamics as well as local culture. This article aims to analyze the application of various camera angle techniques, including close-up, low angle, high angle, and wide shot, in enhancing characterization, conflict, and cultural themes presented in the film. The close-up technique is used to highlight the characters' emotions, while low and high angles strategically depict dominance, power, and vulnerability of the main characters. Additionally, the use of wide shots allows the audience to appreciate the beauty of local culture and the social setting that shapes the story. This study demonstrates how cinematographic techniques, particularly camera angles, can enrich the film's narrative, deepen character development, and reinforce cultural messages. The analysis provides insights into the significance of cinematography in creating an authentic and emotional visual experience in contemporary Indonesian cinema.